Retroperitoneal Tumors in the Pelvis: A Diagnostic Challenge in Gynecology - Wee-Stekly, Wei-Wei; Mueller, Michael David (Frontiers in Surgery, 2014)
Retroperitoneal tumors can pose a diagnostic and therapeutic challenge to gynecologists because of their rarity, late presentation and complex anatomical location in the retroperitoneum. This article reviews the diagnosis and management of retroperitoneal tumors in the pelvis, and highlights the potential pitfalls that may be faced by gynecologists.